IMPLEMENTASI PRODUKSI DAN PENGEMBANGAN WEB UNTUK PEMASARAN PRODUK KREATIF PADA USAHA MANIK LA MAGIE - Firyal Iftinan Dianti; Jonathan Rizky Sitorus; Triantya Wahyu Wirati (CV. Denasya Smart Publisher, 2026)
This study aims to develop a website as a digital marketing tool for the “Manik La Magie” business to enhance customization satisfaction and expand market reach. The method used is a mixed methods approach with a descriptive design, based on a survey of 51 respondents using a 1–4 Likert scale and open-ended questions. The results show that 47.1% of respondents prefer a creative and visually appealing website design, while 64.7% favor digital payment systems. Additionally, there is potential for the use of customization features and interest in interactive workshops. The implementation resulted in a user-friendly website with product catalog, digital payment, customization, and workshop features, which improves transaction convenience, user engagement, and the effectiveness of digital marketing.